The estimation of an anthropogenic depth boundary using the magnetic susceptibility method in Kogi State, North-Central Nigeria - Jatto, Solomon Sunday; Musa, Kizito O; Mojisola, Usikalu R. (Geology, Geophysics and Environment, 2020)
Magnetic susceptibility measurements remain one of the most reliable methods used to investigate the pollution of both surface and subsurface soil from metallic anthropogenic sources. Most of the geological rocks within the study area increase the susceptibility of the soil; however, knowing the natural background susceptibility of the parent rocks will give an idea of the anthropogenic influence on the susceptibility of the soil. This study was carried out in Kogi State, North Central Nigeria, with the aim of determining the depth of the boundary between the anthropogenic influences on soil magnetic susceptibility from those of a lithogenic origin. Magnetic susceptibility measurements were carried out on 1,760 soil samples, collected from 220 soil profiles at a depth of 80.0 cm and at intervals of 10.0 cm. From the spatial distribution of magnetic susceptibility maps at different depths, the boundary between the basement complex and the sedimentary basin was clearly demarcated. The result further shows the highest magnetic susceptibility values of 350–650 × 10−5 SI, which dominates the surface soil to a depth of 40.0 cm. At the depth of 40–50 cm, the result indicates the combination of a natural anthropogenic influence on soil magnetic susceptibility with an average of 250 × 10−5 SI. Furthermore, no evidence of layering along the depth sections was observed, suggesting that the soil profiles indicate areas mainly covered by anthropogenically influenced susceptibility, which were localized and restricted to commercial places within the state. This study reveals that the average depth of soil affected by anthropogenic pollutants is between 40–50 cm in commercial places and 20–30 cm in other places with less commercial activities.